Polish Experience of Kaizen’s Business Development (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The Polish experience in the development of enterprises using Kaizen is considered. The peculiarities of the area of selected Polish companies SYNTHOS S.A., Grupa Spółek LITPOL MALOW, Esselte, Hortimex, DSSE, CMC are presented. The advantages of using Kaizen for employees and firms are determined.Kaizen’s Japanese work philosophy is increasingly being used by Polish companies. It is perfect for organizingproduction processes, ensuring quality and logistics. It allows you to gain competitive advantage through gradual, continuous improvement, setting and achieving higher standards. By implementing Kaizen, the result is also the result of innovative solutions, but in a different way. Without the use of complicated techniques and implementation of modern technologies.SYNTHOS S.A. Is an organization that is development-oriented. The use of Kaizen philosophy in an enterpriseconsists of the use of all employees of the organization, regardless of the position held, thus creating a special working environment. The company LITPOL in Suwalki started its activity since 1990. Manufactured metal furniture for offices, social and educational institutions. In 1998, the enterprise used kaizen in its activities. The goal of introducing Kaizen was to reduce the cost of products and increase product efficiency. The consequence of this was an increase in the competitiveness of products on the domestic and foreign markets.Esselte is the leader in the field of document management and the world’s leading manufacturer of officesupplies. The company was founded in 1913 in Sweden. Esselte has successfully implemented the philosophy of kaizen for the third year already. The company decided to use this method, because because of the huge distribution network, the cost of storing finished products was very high. Kaizen allowed them to optimize the production, administration and internal communications processes.Hortimex is a specialized company providing a platform for the exchange of goods, knowledge and experience between the world’s food ingredients producers and Polish food producers.DSSE is headquartered in Poland in the Walbrzych Special Economic Zone «Invest-Park» LLC in Zharov and has been operating since March 2004. Each member of the Daicel group must fully understand and voluntarily accept the Kaizen Policy and implement it in their daily work.CMC operates in 3 industries specializing in the production of pallets, transportation services and food distribution. The company has been operating on the market since 1991, and its priority is constant development and customer satisfaction.The advantages of kaizen for employees are: kaizen will eliminate unnecessary work and delays in work, allow it to break easily and without irritation; kaizen will facilitate the analysis of your work and help you improve ideas useful to your business, kaizen events provide an opportunity to improve the working environment with the closest employees.Kaizen benefits for the whole company: kaizen eliminates the hidden costs associated with the seven types ofwaste that are present in production processes (overproduction, surplus supply, defects, unnecessary traffic, production losses, waiting, transportation); kaizen allows you to improve performance in order to increase the value of your products so that your customers receive the highest quality, low cost and in the shortest possible time.
Keywords: Kaizen, enterprise, business, benefits, development, experience.